Nuevo método versátil para evaluar preferencia de trips (Thysanoptera) en discos de hojas - De Borbon, Carlos Manuel; Marcucci, Bruno; Mazzitelli, Emilia; Turaglio, María Eugenia; Puebla, Hector Daniel; Navarro, Rosanna Graciela; Baglio, Carla; Lorello, Ines Maria; Mendoza, Graciela Beatriz (Sociedad Entomológica Argentina, 2025)
Poster